Pengembangan Buku Ajar “Pengantar Aljabar” Berorientasi Pada High Order Thinking (HOTS) - Hanim Faizah; Nur Fathonah (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2021)
In Elementer Algebra courses, the students have not been trained to solve problems that are classified in HOTS problems. Therefore, it is need to develop a teaching book that can help students to develop High Order Thinking Skill. This research aims to develop a teaching book entitled "Introduction to Algebra" oriented High Order Thinking Skill (HOTS). This research was research and development. The subjects in this reserach were Mathematics Education student who programmed the Elementer Algebra Course in 2020. The development was carried out using a Four-D development model that developed by Thiagarajan, Semmel, and Semmel 4 stages of development namely Define, Design, Develop, and Disseminate. The textbooks that have been developed are implemented limitedly to 10 students who program Elementer Algebra courses and will then be analyzed qualitatively based on the researcher's Log Book/ Diary, student work results, notes obtained from direct observations during the trial process, test learning results and interview results about the student's response to the book used and the ability of students in high-level thinking (HOTS